Heat and smoke affect the germination of flammable resprouters: Vellozia species in the Cerrado - Zirondi, Heloiza Lourenço [UNESP]; de Pinho José, Henrique [UNESP]; Daibes, L. Felipe [UNESP]; Fidelis, Alessandra [UNESP] (Springer Nature, 2019)
Fire is an important ecological factor shaping plant strategies. Plants that are not able to survive fire and rely on seed reproduction may have seeds adapted for surviving heat shock or their germination may even be enhanced by heat or smoke. In order to find out whether such adaptations may be found in plants able to survive fire and resprout, we examined the germination of ten Vellozia species in response to heat shock and smoke. Seeds were collected in two community types differing in fire frequency: campos sujos (open savannas with frequent and hotter fires) and campos rupestres (montane grasslands on rocky outcrops, with less frequent and milder fires). We hypothesized that seeds of plants inhabiting campos sujos would be more tolerant to fire or will even be stimulated by heat shock or smoke in comparison with seeds of plants inhabiting campos rupestres. We confirmed our expectations only partly, as (i) seeds of all species survived heat shocks of 60 and 100°C for one minute and seeds of three species survived the temperature of 200°C, (ii) the smoke treatments increased germination by 20–40% in three species from both communities, and (iii) mortality after the hottest heat shock was greater in seeds of plants from campos rupestres than from campos sujos. Fire- and smoke-related germination strategies help populations of Vellozia species to cope with recurrent fires in fire-prone ecosystems.
Keywords: Campos rupestres; Fire-related cues; Heat shock; Neotropical savanna; Propagule tolerance; Smoke